TIBIO-FIBULAR BONE TRANSPOSITION FOR THE TREATMENT OF ONCOLOGICAL PERIPROSTHETIC INFECTION OF THE KNEE WITH MASSIVE BONE LOSS - Raffaele Pezzella (Associazione Italiana Giovani Medici, 2021)
Chronic periprosthetic joint infection (PJI) is one of the most relevant complications in orthopaedic surgery, especially in the case of limb reconstruction with megaprostheses after malignant tumoral resection. This is the report of a case of a 35-year-old patient, affected by a chronic PJI around a knee megaprosthesis implanted after the resection of an osteosarcoma of the distal femur. “En bloc” resection and limb reconstruction with an expandable megaprothesis of the knee were performed at the age of 5 years old (1989). PJI occurred after the definitive megaprosthesis implantation (2002), and became chronic over the years. In 2019, due to a massive recrudescence of the infection and the severe femoral bone loss, the patient underwent a wide intercalary resection and a thigh stump reconstruction by transposition of the fibula and the distal third of the tibia in order to avoid a hip disarticulation. Although complex, the proposed treatment allowed improved outcomes in a young patient with high function requests, justifying the global surgical invasiveness.